HISTOPATHOLOGICAL CHANGES IN THE KIDNEY OF COMMON CARP, CYPRINUS CARPIO, FOLLOWING NITRATE EXPOSURE - Iqbal, Furhan; Qureshi, Irfan Zia; Ali, Muhammad (Journal of Research (Science), 2004)
Cyprinus carpio, common carp was exposed to subleathel concentration (12 ppm) of nitrate (KNO3) under acute and chronic static bioassay conditions. The resultant histopathological changes in the liver were recorded by light microscopy. LC50 values of nitrate, according to Reed-Muench method, were 995 ppm for 48 hrs and 865 ppm for 96 hrs. For the acute tests, the fish were exposed to 12 ppm of nitrate for 1,2 and 4 days. For chronic tests, the fish were treated with 12 ppm of nitrate for 8, 16 and 32 days. Control fish were maintained in parallel with the experimental groups. Increase in Bowman’s space, degeneration of glomeruli, shrinkage of proximal tubule cells with pycnotic nuclei, increased tubular lumen and increased in intratubular hematopoietic tissue were the most significant changes observed in fish kidney after nitrate exposure. The effects were time dependent being more pronounced in acute treatments. The present investigation illustrates that presence of high concentration of nitrate in water are stressful to fishes.